Influence of “Gema Cermat” Education to Increased Hb Levels for Pregnant Women in Kediri – East Java - Hanie Kusuma Wardani; Hanni Prihastuti Puspitasari; Yuni Priyandani (Strada Journal of Pharmacy, 2023)
The prevalence of iron deficiency anemia in pregnant women globally reaches 52% in developing countries, including Indonesia. The impact of anemia on pregnant women is premature birth, LBW, bleeding, and even the mother and baby's death. To overcome this, the Indonesian government has ironic-folic acid (IFA) supplementation program for pregnant women with at least 90 tablets during their pregnancy. This program has walked since the 1990s, but anemia in Indonesia is still high (48.9%). Because of these issues, the Ministry of Health gave education for increased use of IFA in pregnant women, namely "Gema Cermat". The purpose of this study is to know the effect of "Gema Cermat" education on increasing Hb levels of pregnant women. This study is a quasi-experimental design, one-group pre-test post-test only, carried out on 41 pregnant women in 3 Primary Health Care Centers in Kediri City. This research measures Hb levels before and after "Gema Cermat" education. Research results in 78% of pregnant women at 20-35 years old, domiciled in Kediri City (98%), level of education is high school (51%). History of multiparous pregnancy (76%), no experience of lack of chronic energy (93%), and increasing Hb level of 1.3g/dl. The Wilcoxon Signed Rank Test analysis results in this study conclude that "Gema Cermat" education is influential in enhancing Hb-level pregnant women.